Society, schools and progress in Scandinavia - Dixon, C. Willis (Cyril Willis) (Commonwealth and international library. Education and educational research., 1965)
Society, Schools and Progress in Scandinavia is one of a mutually supporting series of books on SOCIETY, SCHOOLS AND PROGRESS in a number of important countries or regions. Society, schools, and progress are here surveyed in the world's most significant countries not simply for reasons of technological or political strength, but because of the widely relevant decisions in education now being taken. The present volume is intended to give students and other persons interested in Scandinavia sufficient information and comment to begin to understand the contemporary scene in Denmark, Norway, and S.